HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN RESILIENSI PADA SISWA SEKOLAH MENENGAH PERTAMA - Novi Hidayat; Ziyadi Ali Ikromi (Universitas Sains Indonesia Publishing, 2024)
Resilience is the ability to bounce back positively when faced with stressful conditions. Resilience problems are very likely to arise in early adolescents because they are considered emotionally immature and are very easily affected by changes in their social environment. This study aims to examine the relationship between social support and resilience in early adolescents with subjects of 160 students from a junior high school in Indonesia, obtained by random sampling. Two questionnaires using a Likert scale were used to collect data, namely social support (Cronbach's alpha = 0.879) and resilience (Cronbach's alpha = 0.854). The validity test uses the product moment correlation technique, while the reliability test uses Cronbach's alpha. The data analysis technique uses product moment correlation, which shows rcount > rtable (0.498 > 0.159), so there is a significant relationship between social support and resilience in students. This shows that there is a strong relationship between social support and resilience in students.